Estudo anatômico do lenho e morfologia foliar de Blepharocalyx salicifolius (H. B. K.) Berg, em duas regiões do Rio Grande do Sul - Denardi, Luciano (2004)
The purpose of this work is the description and comparison of wood anatomy and leaf morphology of Blepharocalyx salicifolius (H. B. K.) Berg (Myrtaceae), from two regions in the State Rio Grande do Sul Brazil: Serra do Sudeste and Campos de Cima da Serra . They were collected 6 samples of wood, three from each provenance. The wood microtechnique followed the standard procedures used in the Wood Anatomy Laboratory of the Federal University of Paraná (Curitiba-Brazil). For the maceration of wood samples it was used the Jeffrey method. From each plant, it was also collected leaf branches from different points in the canopy. The main results are listed as follows: the wood anatomy agrees, in general lines, with the typical standard of the family, congregating a big number of narrow and solitary vessels, with simple perforation plates, besides diffuse apotracheal parenchyma, heterogeneous rays and bordered pit fibres. The qualitative features of the wood anatomy do not express differences between the two provenances, with the exception of pith flecks. With respect to the quantitative wood features, on the other hand, they showed important differences about the struture of vessels, axial parenchyma, rays and fibres. For the Serra do Sudeste samples, they were found xeric evidences in the wood (a larger number of small vessels, besides shorter vessel members and fibres), as well as in the leaf morphology (narrower and shorter leaves, with small leaf area), in comparison with those from the Campos de Cima da Serra region. The differences observed in the wood anatomy and leaf morphology may be interpreted as adaptative responses to environment conditions.